2016
DOI: 10.1038/mto.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

N-Myc expression enhances the oncolytic effects of vesicular stomatitis virus in human neuroblastoma cells

Abstract: N-myc oncogene amplification is associated but not present in all cases of high-risk neuroblastoma (NB). Since oncogene expression could often modulate sensitivity to oncolytic viruses, we wanted to examine if N-myc expression status would determine virotherapy efficacy to high-risk NB. We showed that induction of exogenous N-myc in a non-N-myc-amplified cell line background (TET-21N) increased susceptibility to oncolytic vesicular stomatitis virus (mutant VSVΔM51) and alleviated the type I IFN-induced antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…N-Myc overexpression has been shown to enhance VSV replication and oncolysis in human neuroblastoma cells due to inhibition of ISGs [78]. Oncogenic Ras has been shown to promote VSVmediated oncolysis due to inhibition of IRF1 [79].…”
Section: Other Approaches To Improve Vsv Oncoselectivitymentioning
confidence: 99%
“…N-Myc overexpression has been shown to enhance VSV replication and oncolysis in human neuroblastoma cells due to inhibition of ISGs [78]. Oncogenic Ras has been shown to promote VSVmediated oncolysis due to inhibition of IRF1 [79].…”
Section: Other Approaches To Improve Vsv Oncoselectivitymentioning
confidence: 99%
“…In recent years, research has showed that the MYCN gene is an indicator of NB with aggressive progression and a poor prognosis [12,13] . Wang [14] reported that 12% of children with NB had MYCN amplification.…”
Section: Discussionmentioning
confidence: 99%